Screening of crude extracts of six medicinal plants used in South-West Nigerian unorthodox medicine for anti-methicillin resistant Staphylococcus aureus activity - Ibe Christopher C; Okwara Chidi E; Oladapo Olukayode; Akinyemi Kabir O; Fasure Kehinde A (BMC, 2005)
Abstract Background Six Nigerian medicinal plants Terminalia avicennioides, Phylantus discoideus, Bridella ferruginea, Ageratum conyzoides, Ocimum gratissimum and Acalypha wilkesiana used by traditional medical practitioners for the treatment of several ailments of microbial and non-microbial origins were investigated for in vitro anti-methicillin Resistant Staphylococcus aureus (MRSA) activity. Methods Fresh plant materials were collected from the users. Water and ethanol extracts of the shredded plants were obtained by standard methods. The Bacterial cultures used were strains of MRSA isolated from patients. MRSA was determined by the reference broth microdilution methods using the established National Committee for Clinical Laboratory Standards break points. Staphylococcus aureus NCIB 8588 was used as a standard strain. Susceptibility testing and phytochemical screening of the plant extracts were performed by standard procedures. Controls were maintained for each test batch. Results Both water and ethanol extracts of T. avicennioides, P. discoideus, O. gratissimum, and A. wilkesiana were effective on MRSA. The Minimum Inhibition Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of the ethanol extracts of these plants range from 18.2 to 24.0 mcg/ml and 30.4 to 37.0 mcg/ml respectively. In contrast, MIC range of 30.6 to 43.0 mcg/ml and 55.4 to 71.0 mcg/ml were recorded for ethanol and water extracts of B. ferruginea, and A. conyzoides respectively. Higher MBC values were obtained for the two plants. These concentrations were too high to be considered active in this study. All the four active plants contained at least trace amount of anthraquinones. Conclusion Our results offer a scientific basis for the traditional use of water and ethanol extracts of A. wilkesiana, O. gratissimum, T. avicennioides and P. discoideus against MRSA-associated diseases. However, B. ferruginea and A. conyzoides were ineffective in vitro in this study; we therefore suggest the immediate stoppage of their traditional use against MRSA-associated diseases in Lagos, Nigeria.